KARAKTERISTIK FISIKOKIMIA TORTILLA DARI TEPUNG JAGUNG TAMBIN, TEPUNG SAGU DAN TEPUNG UDANG REBON - Rosida, Rosida; Jariyah, Jariyah; Oktalydia, Shelly Panca (Jurnal Teknologi Pangan, 2024)
Tambin corn is a corn variety that is widely cultivated in Madura island and has relatively high starch and beta-carotene content compared to other varieties. This could be an opportunity for tambin corn to be made into processed food products, for example tortilla chips. The aim of this research was to analyze the effect of the proportion of corn flour: sago flour and the addition of rebon shrimp flour on the physicochemical and organoleptic properties of tortella. The design of this research was a Completely Randomized Design (CRD) with a factorial pattern with two factors, namely the proportion of corn flour: sago flour (95:5, 90:10, 85:15) and the addition of rebon shrimp flour (2.5%, 5%, 7.5%). The best treatment is the proportion of tambin corn flour: sago flour (95:5) with the addition of 2.5% rebon shrimp flour which produces chps tortillas with a water content of 6.04%; ash content 2.56%; protein content 6.91%; fat content 3.62%; starch content 60.54%; hardness 356.17gf and average organoleptic results show a taste preference score of 4.2 (like); aroma 3.53 (somewhat like), color 4.10 (like); and texture of 3.47 (rather like it), beta-carotene content of 16.27mg/100g and calcium of 125.8 mg/100 g.